Elements of Success - Susan Burkhauser,, Lawrence M. Hanser, Chaitra M. Hardison (RAND Corporation, 2014)
Aptitude for successful military service in the enlisted ranks includes the ability to succeed in at least one of many military occupational specialties, career fields, or ratings and the ability to adapt to and thrive in a military lifestyle of good order and discipline. The Department of Defense screens military applicants for these qualities using the Armed Forces Qualification Test from the Armed Services Vocational Aptitude Battery, physical and moral standards, and educational credentials. Historically, educational credentials have served as a proxy for the ability to adapt to a military lifestyle. Evidence that supports this use is the stark difference in completion rates for the initial term of service between recruits who hold traditional high school diplomas and those who hold General Educational Development certificates. However, the last few decades have witnessed an explosion of ways to earn education credentials, including homeschooling and distance learning. Therefore, at this juncture, it is important to consider whether these particular education credentials (specifically those for homeschool and distance learning) remain suitable proxies for predicting first-term attrition. This report examines whether the current use of the education tiers better predicts first-term attrition rates than not using education credential information at all. The results should be of interest to Congress and Department of Defense policymakers who set policies for entrance into enlisted military service, as well as to the military services’ recruiting services. This research was sponsored by the Director of Accession Policy in the Office of the Undersecretary of Defense for Personnel and Readiness and conducted within the Forces and Resources Policy Center of RAND’s National Defense Research Institute, a federally funded research and development center sponsored by the Office of the Secretary of Defense, the Joint Staff, the Unified Combatant Commands, the Navy, the Marine Corps, the defense agencies, and the defense Intelligence Community. For more information on the RAND Forces and Resources Policy Center,